PRINSIP-PRINSIP PERILAKU APIP DAN KUALITAS AUDIT - Widodo, Adi Juniarso & (Universitas Slamet Riyadi, 2015)
This study intended to determine the effect of Principles of Behaviour of APIP, which refers to the Permenpan No: PER / 04 / M.PAN / 03/2008, over Audit Quality. Tests were performed on 140 Internal Auditor consisting of Auditor and P2UPD in the former residency Solo Raya region. Datas were collected using questionnaire and analyzed using SmartPLS 2.0.M3 program. The results showed that the three principles of behavior of Integrity, Confidentiality and Competence affected audit quality, but the test results showed that the principle of objectivity has no effect. The test results are likely due to the context of Java politeness